Biological assessment of western USA sandy bottom rivers based on modeling historical and current fish and macroinvertebrate data. (11th January 2022) - Hughes, Robert M.; Zeigler, Meredith; Stringer, Shann; Linam, Gordon W.; Flotemersch, Joseph; Jessup, Benjamin; Joseph, Seva; Jacobi, Gerald; Guevara, Lynette; Cook, Robert; Bradley, Patricia; Barrios, Kristopher
Abstract: Biological monitoring is important for assessing the ecological condition of surface waters. However, there are challenges in determining what constitutes reference conditions, what assemblages should be used as indicators, and how assemblage data should be converted into quantitative indicator scores. In this study, we developed and applied biological condition gradient (BCG) modeling to fish and macroinvertebrate data previously collected from large, sandy bottom southwestern USA rivers. Such rivers are particularly vulnerable to altered flow regimes resulting from dams, water withdrawals and climate change. We found that sensitive ubiquitous taxa for both fish and macroinvertebrates had been replaced by more tolerant taxa, but that the condition assessment ratings based on fish and macroinvertebrate assemblages differed. We conclude that the BCG models based on both macroinvertebrate and fish assemblage condition were useful for classifying the condition of southwestern USA sandy bottom rivers. However, our fish BCG model was slightly more sensitive than the macroinvertebrate model to anthropogenic disturbance, presumably because we had historical fish data, and because fish may be more sensitive to dams and altered flow regimes than are macroinvertebrates.